Planning for Megaevents, dual dedications of legacy and delivery - Vadiati, Niloufar (International Planning History Society Proceedings, 2018)
Mega-events as ‘hallmark event’ (Essex&Chalkley 1998) are considered as a means of image building, and catalyst for urban economic regeneration and development through strategies of attracting global investment, high employment multipliers and local tax revenues (Owen 2002). Critics, however, emphasise that running a 'spectacle' and achieving local regeneration are tasks which are not easily reconciled (Eisinger 2000), since the consumers of the spectacle are mainly middle-class (Gornostaeva 2011), and the ultimate consequences of city renewal by means of sport/consumption-led regeneration will be gentrification, prising-out and displace local small businesses and the disadvantaged populations (Vigor, Mean et al. 2004, Cohen& Watt 2017). I suggest that there are common dynamics behind the controversy of hosting the Mega Events which has plagued almost everywhere in the world to a greater or lesser degree, as the contradiction between two concurrent and tacit conceptions of the Mega Events. Delivery: the conception that understands the games as a project that should get done on time and perfect alongside, and as the counterpoint, legacy, which conceives Mega Event as a tool of redistributing the benefits to the citizens. The combination of legacy and delivery or public-sector (gift) and private-sector (profit) in one phrase seems awkward at best and an outright oxymoron at worst, while can be only explained by the market base city development. Therefore, the aim of this paper presentation is to review and analyse the whole process of Mega Event planning and legacy building which has been set to deliver the whole event and engage the locals to the benefits, while reflecting them on recent urban discourses, and the theories embedded them.